2017
DOI: 10.1371/journal.pone.0177521
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary supplementation (Rosmarinus oficinallis L.) attenuates cardiac remodeling after myocardial infarction in rats

Abstract: BackgroundMyocardial infarction (MI) is one of the leading causes of morbidity and mortality worldwide. Dietary intervention on adverse cardiac remodeling after MI has significant clinical relevance. Rosemary leaves are a natural product with antioxidant/anti-inflammatory properties, but its effect on morphology and ventricular function after MI is unknown.Methods and resultsTo determine the effect of the dietary supplementation of rosemary leaves on cardiac remodeling after MI, male Wistar rats were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 64 publications
2
20
0
1
Order By: Relevance
“…The effect of the supplementation with R. officinalis L . leaves was evaluated on cardiac remodeling after myocardial infarction in male Wistar rats [47]. For this, healthy animals and infarcted animals were fed with standard chow or chow containing 0.02% or 0.2% of R. officinalis L. leaves for 90 days.…”
Section: Cardiac Remodeling After Myocardial Infarctionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of the supplementation with R. officinalis L . leaves was evaluated on cardiac remodeling after myocardial infarction in male Wistar rats [47]. For this, healthy animals and infarcted animals were fed with standard chow or chow containing 0.02% or 0.2% of R. officinalis L. leaves for 90 days.…”
Section: Cardiac Remodeling After Myocardial Infarctionmentioning
confidence: 99%
“…Molecular and cellular changes in the heart are responsible for the clinical problems. Thus, metabolic pathways and antioxidants could be the interaction forms of R. officinalis L. with living tissue [47, 48].…”
Section: Cardiac Remodeling After Myocardial Infarctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have already reported that antioxidants are beneficial after injury to the myocardium since they increase the force of myocardial contraction, increase coronary flow, limit the size of infarction, and prevent mortality. This protective effect is associated with the decrease in oxygen free radicals that can activate the production of inflammatory cytokines and the release of human neutrophil elastase from neutrophils [ 55 , 56 ]. It would be desirable to determine whether treatment with polyphenols could modify other processes such as: cellular K + concentration, the duration of the potential, development of systolic strength, levels of high energy phosphate, and damage to the cellular metabolic machinery [ 57 ].…”
Section: Discussionmentioning
confidence: 99%